Pelvic congestion syndrome - Sultana, Razia; Begum, Rowshan Ara; Begum, Ferdousi (Mediscope, 2015)
Chronic pelvic pain is a common gynecological problem with many causes and may account for approximately 10% outpatient gynecological visit. Pelvic Congestion Syndrome (PCS) is defined as a condition characterized by congestion of the pelvic veins visible on selective ovarian venography in multiparous premenopausal women with a history of chronic pelvic pain for more than six months. We report a case of PCS in 35 years old multiparous lady complaining of chronic pelvic pain for one year. The pain was worsened by sitting and standing position. Other general symptoms were present such as dysmenorrhea, rectal discomfort and urinary frequency. On examination patient was depressed, there was abdominal and pelvic tenderness. Pelvic ultrasound and Doppler examination showed dilated and tortuous ovarian veins and dilated tortuous arcuate veins in the myometrium. An ovarian cyst was present and uterus was enlarged. In this case total abdominal hysterectomy was done although ideal treatment for PCS is ovarian vein embolisation by interventional radiology which is not available in our country. DOI: http://dx.doi.org/10.3329/mediscope.v1i1.21635 Mediscope Vol. 1, No. 1: 2014, Pages 33-35